High-ion-conductivity cement-based structured electrolyte and preparation method thereof

By using temperature controlled mixing and low-temperature maintenance technology of polymer solution and cement in cement based electrolytes, the problem of low ion conductivity of cement based electrolytes is solved, and high ion conductivity and good mechanical properties are achieved.

CN119638304AActive Publication Date: 2025-03-18SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411570929.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Due to problems such as low ion conductivity and high resistance, it is difficult to achieve both high mechanical bearing strength and high ion conductivity.

Method used

By finely mixing the polymer solution, cement and fine sand under temperature controlled conditions, a polymer-cement slurry is formed, and a process of low-temperature sealed curing and room temperature stand-alone is adopted to use the elastic phase separation characteristics of the polymer to form a cement-based structured electrolyte with high ionic conductivity.

Benefits of technology

The high ion conductivity and good mechanical properties of cement-based structure electrolytes were achieved. The compressive strength and flexural strength could reach more than 80% and more than 90% of the same proportional commercial control group, and the ion conductivity could reach more than 300mS/cm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638304A_ABST
    Figure CN119638304A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cement-based structured electrolyte with high ion conductivity and the electrolyte, and the preparation method comprises the following steps: mixing a polymer solution, cement and fine sand to obtain a polymer-cement paste; and performing low-temperature closed maintenance on the polymer-cement paste, and standing at room temperature to obtain the cement-based structured electrolyte. The controlled phase separation technology is adopted, elastic phase separation of a polymer network is carried out earlier than cement hydration, cement becomes a framework of the polymer network in a self-adaptive mode in the hydration process, the interface of the polymer network and the cement is good, and a continuous high-conduction ion channel can be formed; and the preparation process is simple to operate and high in repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional composite materials, and in particular to a high ion conductivity cement-based structured electrolyte and a preparation method thereof. Background Art

[0002] The advanced building materials of the future should have multifunctional intelligent properties, such as collecting and storing renewable energy such as solar and wind energy. Using structures and buildings as energy storage devices has great innovative significance. Due to the large volume of buildings, even if the energy storage density per unit volume of the new generation of building materials is not high, its energy storage potential is considerable. However, the low ion conductivity and high resistance of cement have seriously hindered the development of cement-based electrolytes. Existing cement-based electrolytes usually use expensive carbon nanotubes as internal fillers in cement to improve the ion conductivity of cement, but the uniformity of the filler dispersion is difficult to ensure. Uneven carbon nanotubes can easily lead to the formation of weak surfaces in cement, which in turn causes a sudden drop in strength. It is still very difficult to achieve a cement-based structural electrolyte with both high mechanical bearing strength and high ion conductivity. Summary of the invention

[0003] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, an object of the present invention is to provide a cement-based structured electrolyte with high ion conductivity and a preparation method thereof.

[0004] The purpose of the present invention is achieved through the following technical solutions:

[0005] A method for preparing a cement-based structured electrolyte with high ionic conductivity, comprising:

[0006] The polymer solution, cement and fine sand are mixed to obtain a polymer-cement slurry;

[0007] The polymer solution is obtained by dissolving a polymer and a strong base in water, or by dissolving a polymer, a strong base and a sulfide in water, or by dissolving a polymer, a strong base, an inorganic sulfide and a chemical cross-linking agent in water;

[0008] The polymer-cement slurry is subjected to low-temperature sealed curing and then allowed to stand at room temperature to obtain a cement-based structured electrolyte.

[0009] Furthermore, the polymer is one or more of PVA or PAA; the strong base is one or more of KOH and NaOH; the sulfide is one or more of Na2S or K2S; the chemical crosslinking agent is one or more of TEAC (tetraethylammonium chloride) and PEGDGE (polyethylene glycol diglycidyl ether).

[0010] Further, the following steps are included:

[0011] Stir the polymer solid, strong base and water at a temperature of 85-95 degrees and a speed of 250-260 r / min for 1.5-2 hours to prepare a uniform polymer solution;

[0012] Mix cement and fine sand at a speed of 60-70 r / min, and dry mix for 5-10 minutes at a temperature of 90-95 degrees to obtain a cement-fine sand mixture;

[0013] The polymer solution is mixed with the cement and fine sand mixture at a mixing temperature of 90-95 degrees, so that the polymer solution is evenly dispersed in the cement to obtain a polymer-cement slurry;

[0014] The polymer-cement slurry is then cooled to 2-5 degrees, and the cooling process takes 5-10 minutes. During the cooling process, the cement slurry is stirred at a constant speed, and 60-80g of deionized water at 2-5 degrees is slowly added to obtain a cement slurry containing a liquid-solid mixed phase; the slow addition speed refers to an addition speed of 0.3-0.5g / s.

[0015] The cement paste containing the liquid-solid mixed phase is placed in a closed environment for curing to obtain a hardened low-temperature cement-based electrolyte;

[0016] The low-temperature cement-based electrolyte is allowed to stand at room temperature for 12-24 hours to form a fully solid cement-based structured electrolyte.

[0017] Furthermore, the cement slurry is stirred at a constant speed during the cooling process, and the constant stirring speed is the same as the stirring speed in the step of obtaining the polymer-cement slurry.

[0018] Furthermore, the cement slurry containing the liquid-solid mixed phase is placed in a closed environment for curing, the temperature of the closed environment is 0-2 degrees, and the curing time is 6-24 hours.

[0019] Furthermore, the constant speed stirring time is 15-20 min.

[0020] Further, the polymer solution is mixed with the cement fine sand mixture at a stirring speed of 140±5 r / min for 1 min 30 s-2 min.

[0021] Furthermore, when the polymer solution contains inorganic sulfide, the inorganic sulfide is added together with the cold water; when the polymer solution contains a chemical crosslinking agent, the chemical crosslinking agent is added together with the cold water;

[0022] The amount of each substance in the polymer solution is calculated by weight:

[0023] Polymer 8-10 parts

[0024] 30-40 parts of strong alkali

[0025] 190-210 parts water

[0026] When inorganic sulfide is contained, the amount of sulfide is 0.5-1 part;

[0027] When a chemical crosslinking agent is contained, the amount of the chemical crosslinking agent is 0.1-0.5 parts;

[0028] When the polymer solution is mixed with cement and fine sand, cement: 490-510 parts; fine sand: 140-160 parts.

[0029] A load-bearing and high ion conductivity integrated cement-based structural electrolyte is prepared by the preparation method.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] The present invention uses a polymer solution to be finely mixed with cement and fine sand under temperature-controlled conditions to obtain a polymer-cement slurry, and utilizes the elastic phase separation characteristics of the polymer in combination with two-stage curing to obtain an electrolyte;

[0032] The present invention mixes the polymer solution and the cement sand system at 90-95 degrees, with a rotation speed of 140+-5r / min and maintained for 1min30s-2min. In this process, the polymer solution is quickly and evenly dispersed into the cement. At the same time, due to the 90-95 degree environment, the solubility of the polymer in the solution is relatively high, and the polymer solid phase network will not precipitate early in the mixing process, thereby avoiding the formation of mechanical weak surfaces of the cement. At the same time, the short and continuous stirring prevents the cement from hardening, thereby obtaining a polymer-cement high-temperature mixed slurry with good fluidity and uniformity.

[0033] The present invention cools and stirs the cement paste. In this process, due to the rapid drop in temperature, the solubility of the polymer in the liquid phase decreases, while the fluidity of the cement does not change significantly. The polymer undergoes elastic phase separation in the completely elastic cement paste liquid phase environment, so that a polymer network of a liquid-solid mixed phase is gradually formed inside the cement. The polymer network is both an ion channel inside the electrolyte and an attachment surface for cement hardening nucleation in the subsequent step.

[0034] The present invention adopts low-temperature closed environment curing, which ensures that the humidity will not change suddenly. In this process, the cement begins to transform into a solid phase and harden to form nuclei. In the second step, the liquid phase part of the polymer liquid-solid mixed phase network will continue to separate from the liquid phase, so that the complete polymer solid phase network is continuously distributed in three-dimensional space. The liquid phase cement and the liquid phase polymer are synchronously transformed into a solid state in this process, that is, the two-phase synchronous in-situ phase separation, and finally a cement-based structural electrolyte with a stable polymer cement interface is formed. This good interface not only avoids the mechanical weak surface caused by the dense precipitation of PVA, but also enhances the synergistic ion conduction performance of cement-polymer. Its compressive strength and flexural strength can reach 80% and 90% of the commercial control group with the same ratio, respectively, and the ion conductivity can reach more than 300mS / cm.

[0035] The present invention adopts low-temperature closed environment curing and then standing at room temperature. During this process, as the temperature rises, the intensity of the hydration reaction increases, and the remaining free water in the cement will participate in further hydration, releasing hydration heat, so that the local temperature of the polymer solid phase network increases, and a small part of the polymer solid phase network will be redissolved in the free water. As the free water is consumed in the hydration reaction, the polymer dissolved in this process will be phase-separated again in the post-hydrated cement, and finally a fully solid cement-based electrolyte with a uniformly distributed polymer network is formed.

[0036] The present invention adopts controlled phase separation technology to make the elastic phase separation of the polymer network proceed earlier than the cement hydration. The cement adaptively becomes the skeleton of the polymer network during the hydration process. The two have a good interface and can form a continuous high-pass ion channel. The preparation process is simple to operate and highly repeatable. The drugs used are all non-toxic and harmless substances, which are environmentally friendly and inexpensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1(a)-Figure 1(f) The EIS result diagrams of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are respectively;

[0038] Figure 2 Schematic diagram of LSV window of Comparative Example 3, Comparative Example 1 and Example 1;

[0039] Figure 3 This is a CV test diagram of an embodiment of the present invention;

[0040] Figure 4 CT schematic diagram of the electrolyte of the present invention. DETAILED DESCRIPTION

[0041] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0042] Example 1

[0043] The polymer solution used in this embodiment 1 is PVA-KOH.

[0044] A method for preparing a cement-based structured electrolyte with high ion conductivity, the preparation process is as follows: 10g PVA is dissolved in 90g deionized water, heated in a water bath at 95 degrees and stirred at 250r / min for 50min; during the stirring period, another beaker is taken to dissolve 30g KOH solid in 110g water to obtain a KOH solution, and when the PVA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution is transparent and light yellow, thereby obtaining a PK solution. 490g cement (PO42.5R) and 140g fine sand are premixed at 70r / min for 10min under a 90-degree environment, the cement and fine sand mixture is added to the PK solution at 90 degrees, and stirred at 145r / min for 2min. After the process is completed, the cooling machine is turned on and 60g deionized water at 2 degrees is slowly added to reduce the slurry temperature to 2 degrees, and stirred at 145r / min for 16min to obtain a polymer-cement slurry. The polymer-cement paste was sealed and cured at 2 degrees for 24 hours and then cured at room temperature for 24 hours to obtain a cement-based structural electrolyte.

[0045] Example 2

[0046] The polymer solution used in this Example 2 is PVA-PAA-KOH.

[0047] A method for preparing a cement-based structured electrolyte with high ion conductivity, the preparation process is as follows: 7.8g PVA and 0.2g PAA are dissolved in 90g deionized water, heated in a water bath at 85 degrees and stirred at 260r / min for 50min; during the stirring period, another beaker is taken to dissolve 40g KOH solid in 115g water to obtain a KOH solution, and when the PVA / PAA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 70min until the mixed solution is transparent and light yellow, thereby obtaining a PKA solution. 510g cement (PO42.5R) and 160g fine sand are premixed at 65r / min for 8min at 95 degrees, the cement and fine sand mixture is added to the PKA solution at 95 degrees, and stirred at 140r / min for 1min30s. After the process is completed, the cooling machine is turned on and 80g deionized water at 5 degrees is slowly added to reduce the slurry temperature to 5 degrees, and the slurry is stirred at 140r / min for 20min to obtain a polymer-cement slurry. The polymer-cement paste was sealed and cured at 0 degrees for 6 hours and then cured at room temperature for 12 hours to obtain a cement-based structured electrolyte.

[0048] Example 3

[0049] In this embodiment 3, the polymer solution used is PVA-KOH-K 2S.

[0050] A cement-based structured electrolyte, the preparation process is as follows: 9.8g PVA is dissolved in 90g deionized water, heated in a water bath at 92 degrees and stirred at 255r / min for 40min; during the stirring period, take another beaker and dissolve 33.6g KOH solid in 110g water to obtain a KOH solution, and when the PVA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution is transparent and light yellow, to obtain a PK solution. In a 92-degree environment, 500g cement (PO42.5R) and 150g fine sand are premixed at 60r / min for 5min, and the cement and fine sand mixture is added to the PK solution at 92 degrees, and stirred at 135r / min for 1min45s. After this process, turn on the cooler and slowly add 65g deionized water at 3 degrees and 0.8g K 2 S, the slurry temperature was lowered to 3 degrees, and the mixture was stirred at 135 r / min for 18 minutes to obtain a polymer-cement slurry. The polymer-cement slurry was sealed and cured at 1 degree for 21 hours, and then cured at room temperature for 18 hours to obtain a cement-based structural electrolyte.

[0051] Comparative Example 1

[0052] Compared with Example 1, the polymer solution is PVA-KOH, there is no cooling process, it is directly mixed and stirred, and then placed in an environment of 2 degrees for curing.

[0053] A cement-based structured electrolyte, the preparation process is as follows: 10g PVA is dissolved in 90g deionized water, heated in a water bath at 95 degrees and stirred at 250r / min for 50min; during the stirring period, another beaker is taken to dissolve 33.6g KOH solid in 110g water to obtain a KOH solution, and when the PVA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution is transparent and light yellow, to obtain a PK solution. 500g cement (PO42.5R) and 150g fine sand are premixed at 70r / min for 10min at 90 degrees, and the cement fine sand mixture and 65g normal temperature deionized water are added to the PK solution at room temperature, and stirred at 145r / min for 18min to obtain a polymer-cement paste. The polymer-cement paste is sealed and cured for 24h within a range of 2 degrees, and then cured at room temperature for 24h to obtain a cement-based structured electrolyte.

[0054] Comparative Example 2:

[0055] Compared with Example 1, the polymer solution is PVA-KOH, there is a cooling process, and curing is carried out at room temperature.

[0056] A cement-based structured electrolyte, the preparation process is as follows: 10g PVA is dissolved in 90g deionized water, heated in a water bath at 95 degrees and stirred at 250r / min for 50min; during the stirring period, another beaker is taken to dissolve 33.6g KOH solid in 110g water to obtain a KOH solution, and when the PVA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution is transparent and light yellow, to obtain a PK solution. 500g cement (PO42.5R) and 150g fine sand are premixed at 70r / min for 10min under a 90-degree environment, and the cement and fine sand mixture is added to the PK solution at 95 degrees, and stirred at 145r / min for 2min. After this process is completed, the cooling machine is turned on and 65g deionized water at 2 degrees is slowly added to reduce the slurry temperature to 2 degrees, and stirred at 145r / min for 16min to obtain a polymer-cement slurry. The polymer-cement slurry is sealed and cured at room temperature for 48h to obtain a cement-based structured electrolyte.

[0057] Comparative Example 3:

[0058] Compared with Example 1, the polymer solution is PVA-KOH, there is no cooling process, and the curing is carried out at room temperature.

[0059] A cement-based structured electrolyte, the preparation process is as follows: 10g PVA is dissolved in 90g deionized water, heated in a water bath at 95 degrees and stirred at 250r / min for 50min; during the stirring period, another beaker is taken to dissolve 33.6g KOH solid in 110g water to obtain a KOH solution, and when the PVA solution is light milky white, the KOH solution is slowly dripped into the PVA solution and kept heated and stirred for 50min until the mixed solution is transparent and light yellow, to obtain a PK solution. 500g cement (PO42.5R) and 150g fine sand are premixed at 70r / min for 10min at 90 degrees, and the cement-fine sand mixture and 65g deionized water at room temperature are added to the PK solution, and stirred at 145r / min for 18min to obtain a polymer-cement slurry. The polymer-cement slurry is sealed and cured at room temperature for 48h to obtain a cement-based structured electrolyte.

[0060] Performance Test:

[0061] like Figure 1(a)-Figure 1(f) As shown, it reflects the ionic conductivity of the electrolyte. The higher the ionic conductivity, the better the performance of the electrolyte.

[0062] From the EIS results, it can be seen that the conductivity of Example 1 is 108mS / cm, the conductivity of Example 2 is 303mS / cm, the conductivity of Example 3 is 165.6mS / cm, the conductivity of Comparative Example 1 is 63.3mS / cm, the conductivity of Comparative Example 2 is 1.926mS / cm, and the conductivity of Comparative Example 3 is 0.166mS / cm.

[0063] It can be seen from Examples 1-3 that the ion conductivity of the cement-based structured electrolyte with cooling stirring and low-temperature curing is on the order of 102 mS / cm.

[0064] From the comparison between Example 1 and Comparative Example 1, it can be seen that the ion conductivity decreases by 41.4% due to the lack of cooling and stirring.

[0065] From the comparison between Example 1 and Comparative Example 2, it can be seen that the ion conductivity decreases by 98.2% due to the lack of low-temperature maintenance.

[0066] From the comparison between Example 1 and Comparative Example 3, it can be seen that the ion conductivity is reduced by 99.8% due to the lack of cooling, stirring and low-temperature curing. That is, the product formed by directly mixing the polymer solution and cement does not have the ability to serve as an electrolyte.

[0067] like Figure 2 As shown in the LSV window diagram, the longer the window, the more stable the electrolyte.

[0068] like Figure 2 It can be seen that the electrolyte in Example 1 of the present invention with cooling, stirring and low-temperature curing is the most stable.

[0069] like Figure 3 As shown, the test method is that of Examples 1-3 and Comparative Examples 1-3, respectively, use the same nickel-iron pole piece for assembly test, apply a linearly changing potential (voltage), and monitor the corresponding current response. Comparative Example 1 (no cooling and stirring, with 2-5 degree curing) and Comparative Example 3 (no cooling and stirring, no 2-5 degree curing) do not have the reaction peaks shown in Example 1. The reaction peaks 0.74V and 1.00V correspond to the reduction reaction of the iron pole, and 1.65V corresponds to the oxidation reaction of the nickel pole. Only in Example 1 (both cooling and constant speed stirring, and 2-5 degree curing electrolyte) has a complete reaction peak, which proves the feasibility of applying this electrolyte to all-solid-state alkaline batteries. This shows the superiority of the temperature-controlled originally phase-separated cement-based structured electrolyte proposed by the present invention in supporting the electrical reaction of all-solid-state batteries.

[0070] like Figure 4 This is a CT image of the electrolyte prepared by the preparation method of the present invention, which can intuitively show the distribution of the PK network inside the cement.

[0071] Table 1 shows the mechanical properties of the electrolytes prepared in Examples 1 to 3, indicating that the electrolytes have good load-bearing capacity in terms of axial compression and flexural stress.

[0072] Table 1 Mechanical strength

[0073]

[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a cement-based structured electrolyte with high ionic conductivity, characterized in that: include: The polymer solution, cement and fine sand are mixed to obtain a polymer-cement slurry; The polymer solution is obtained by dissolving a polymer and a strong base in water, or by dissolving a polymer, a strong base and a sulfide in water, or by dissolving a polymer, a strong base, an inorganic sulfide and a chemical cross-linking agent in water; The polymer-cement slurry is subjected to low-temperature sealed curing and then allowed to stand at room temperature to obtain a cement-based structured electrolyte.

2. The preparation method according to claim 1, characterized in that: The polymer is one or more of PVA and PAA; the strong base is one or more of KOH and NaOH; the sulfide is one or more of Na2S and K2S; the chemical cross-linking agent is one or more of tetraethylammonium chloride and polyethylene glycol diglycidyl ether.

3. The preparation method according to claim 1, characterized in that: The steps include: Mix the polymer solid, strong base and water, and stir at a temperature of 85-95 degrees and a speed of 250-260 r / min for 1.5-2 hours to prepare a uniform polymer solution; Mix cement and fine sand, at a temperature of 90-95 degrees, at a speed of 60-70 r / min, and dry mix for 5-10 minutes to obtain a cement-fine sand mixture; The polymer solution is mixed with the cement and fine sand mixture at a mixing temperature of 90-95 degrees, so that the polymer solution is evenly dispersed in the cement to obtain a polymer-cement slurry; Then the polymer-cement slurry is cooled to 2-5 degrees, the cooling process takes 5-10 minutes, the cement slurry is stirred at a constant speed during the cooling process, and 60-80g of water at 2-5 degrees is slowly added to obtain a cement slurry containing a liquid-solid mixed phase; The cement paste containing the liquid-solid mixed phase is placed in a closed environment for curing to obtain a hardened low-temperature cement-based electrolyte; The low-temperature cement-based electrolyte is allowed to stand at room temperature for 12-24 hours to form a fully solid cement-based structured electrolyte.

4. The preparation method according to claim 3, characterized in that: The cement slurry is stirred at a constant speed during the cooling process, and the constant stirring speed is the same as the stirring speed in the step of obtaining the polymer-cement slurry.

5. The preparation method according to claim 3, characterized in that: The cement slurry containing the liquid-solid mixed phase is placed in a closed environment for curing, the temperature of the closed environment is 0-2 degrees, and the curing time is 6-24 hours.

6. The preparation method according to claim 3, characterized in that: The constant speed stirring time is 15-20min.

7. The preparation method according to claim 3, characterized in that: The polymer solution is mixed with the cement fine sand mixture at a stirring speed of 140±5r / min and a stirring time of 1min30s-2min.

8. The preparation method according to claim 1, characterized in that: When the polymer solution contains inorganic sulfide, the inorganic sulfide is added together with water; when the polymer solution contains a chemical cross-linking agent, the chemical cross-linking agent is added together with water.

9. The preparation method according to claim 1, characterized in that: The amount of each substance in the polymer solution is calculated by weight: 8-10 parts of polymer; 30-40 parts of strong alkali; 190-210 parts of water; When inorganic sulfide is contained, the amount of sulfide is 0.5-1 part; When a chemical crosslinking agent is contained, the amount of the chemical crosslinking agent is 0.1-0.5 parts; When the polymer solution is mixed with cement and fine sand, cement: 490-510 parts; Fine sand: 140-160 parts.

10. A high ionic conductivity cement-based structured electrolyte, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Self-repairing polymer cement waterproof paint and preparation method thereof

    CN111574126A

  • Polyacrylamide / magnesium phosphate cement composite solid electrolyte, preparation method thereof and structural supercapacitor

    CN115424872A

  • Polymer-cement-metal salt solid electrolyte, preparation method thereof and structural energy storage device

    CN116768561A

  • Polymer modified cement-based patching material and preparation method thereof

    CN118529983A

  • Method for producing hardened cement body, and hardened cement body

    JP2010083698A

Cited By

  • Bearing and energy storage integrated cement-based structure battery and preparation method thereof

    CN119674274A

  • A cement-based structural battery with integrated load-bearing and energy storage function and its preparation method

    CN119674274B